The Implementation of Neurological Impress Method (NIM) on the Students' Reading Comprehension at the Eight Grade of SMPN 33 Makassar - Kasma; Anugrawati, Nunung; Firman (Journal of Language Testing and Assessment, 2025)
This research was attempted to improve students’ reading comprehension by using Neurological Impress Method (NIM). This study was conducted by using pre-experimental research. The object of the research was VIII.A grade SMPN 33 Makassar consist of 25 students. The research was conducted four meetings and three steps. The first meet, the researcher explained about the Neurological Impress Method (NIM) and how to uses this method, the second the researcher gave pre-test, and then gave treatment, and the last meet gave post-test. The instruments of collecting data were reading test. Based on the reading test score, students’ score kept improving in every test. In the pre-test the mean was 56, and in the port test the mean was 68. It proved that using Neurological Impress Method (NIM) to improve students’ reading comprehension showed significant result by improving around 12.6%. It was found that teaching learning process ran well. Students were active and interested in reading. The result of this research showed that Neurological Impress Method (NIM) can improve students ability in reading comprehension.